Effects of teaching games for understanding approach on students' learning outcomes / Malathi Balakrishnan - Balakrishnan, Malathi (2011)
The present study investigated the effects of Teaching Games for Understanding (TGfU) approach on students’ learning outcomes. The study employed a quasi-experimental non-equivalent pretest-posttest control group design. Seventytwo (72) year four primary school physical education students from four intact classes were randomly assigned to an experimental group (n = 36) and a control group (n = 36). The experimental group students were exposed with TGfU approach and the control group students were with the Traditional Skill approach for handball game. The research was carried for six weeks in a primary physical education school setting. Research instruments used in this study were the Game Performance Assessment Instrument (GPAI) to measure students’ tactical understanding and decision making in 3 versus 3 game situations; Situational Motivational Scale Instrument to evaluate students’ motivation after the game session and 30 meter handball dribbling skill test to measure students’ skill performance. Reliability and validity of the instruments were assessed in the pilot study. Quantitative data were analyzed using Analysis of covariance (ANCOVA) and Mann-Whitney U test. Further focus group interview data were transcribed, coded and analyzed with cross-case analysis. The major findings of this study revealed that there was a significant main effect of treatment on students’ learning outcome. ANCOVA analysis revealed that there was significant main effect of TGfU approach on students’ cognitive learning outcome (F (1, 69) = 248.83, p < .05). Also it showed that there were significant main effects of TGfU approach on students’ psychomotor learning outcome (F (1, 69) =37.44, p < .05). The Mann- Whitney U test result revealed students’ situational motivation was significant: U = 35.5, z = -6.95, p < .05. The TGfU approach group students had an average mean rank of 53.5 compared to traditional skill approach students’ average mean rank of 19.40. The result showed that the TGfU approach enhances students’ situational motivation in handball game. The evidence gathered from the qualitative data showed that students with TGfU had better cognitive understanding in decision making and problem solving ability compared to students taught under the traditional skill approach. The findings of this study have theoretical significance as well as pedagogical implications. In addition the findings of this study suggested the importance of TGfU approach to improve primary student’s tactical understanding and decision making in handball. This study also helps to inform a better physical education game learning approach for students and provide suggestion for future research using TGfU approach.